The influence of female academic leaders in higher education institutions on achieving Saudi Vision 2030 - Hasna Balaj Albaroudi Alotaibi (Revista on line de Política e Gestão Educacional)
Education is an essential element to the development of nations. Accordingly, Saudi Arabia has invested heavily in the development of its education sector. Nevertheless, continuous development of education, especially the higher education sector, significantly depends on the quality and adequate supply of leadership that cuts across the gender divide. However, analysis of the literature indicates a lack of discussion on the leadership role of women in Saudi higher educational institutions. This paper reviews the opportunities and challenges against female academic leadership in Saudi higher education institutions and their influence towards achieving the Saudi Vision 2030. An eclectic scoping review was adopted to synthesize the relevant materials published in the past ten years in the context of Saudi Arabia. The findings indicate that the main obstacles to female academic leaders include structural challenges, shortage of resources, and lack of empowerment, with personal and cultural challenges ranked last.